Reviving hope – the journey of diagnosing and treating Guillain-Barré syndrome - Oleszczuk, Anna; Kozieł, Julia; Kosmala, Szymon; Kufrejska, Noemi; Hawranik, Paweł; Jurkiewicz, Katarzyna; Kurek, Marcelina; Chrościńska-Krawczyk, Magdalena (Pediatria Polska - Polish Journal of Paediatrics, 2025)
The Guillain-Barré syndrome (GBS) is a rare but serious neurological condition that continues to pose diagnostic and therapeutic challenges, particularly in paediatrics. Although most paediatric patients achieve full recovery, some experience persisting complications such as chronic pain, paraesthesia, or reduced physical capacity. This study provides a comprehensive review of GBS, addressing its epidemiology, pathogenesis, clinical symptoms, as well as diagnostic and therapeutic tools. An integrated treatment approach, encompassing both causal and symptomatic therapies, plays a pivotal role in the recovery process. In recent years, novel biologic therapies, such as eculizumab and efgartigimod, have emerged as promising treatment options. However, further research is required, especially within the context of the paediatric population.